Challenges in Fluorescence Detection of Chemical Warfare Agent Vapors Using Solid‐State Films. Issue 18 (6th November 2019) - Fan, Shengqiang; Zhang, Guanran; Dennison, Genevieve H.; FitzGerald, Nicholas; Burn, Paul L.; Gentle, Ian R.; Shaw, Paul E.
Abstract: Organophosphorus (OP)‐based nerve agents are extremely toxic and potent acetylcholinesterase inhibitors and recent attacks involving nerve agents highlight the need for fast detection and intervention. Fluorescence‐based detection, where the sensing material undergoes a chemical reaction with the agent causing a measurable change in the luminescence, is one method for sensing and identifying nerve agents. Most studies use the simulants diethylchlorophosphate and di‐ iso ‐propylfluorophosphate to evaluate the performance of sensors due to their reduced toxicity relative to OP nerve agents. While detection of nerve agent simulants in solution is relatively widely reported, there are fewer reports on vapor detection using solid‐state sensors. Herein, progress in organic semiconductor sensing materials developed for solid‐state detection of OP‐based nerve agent vapors is reviewed. The effect of acid impurities arising from the hydrolysis of simulants and nerve agents on the efficacy and selectivity of the reported sensing materials is also discussed. Indeed, in some cases it is unclear whether it is the simulant that is detected or the acid hydrolysis products. Finally, it is highlighted that while analyte diffusion into the sensing film is critical in the design of fast, responsive sensing systems, it is an area that is currently not well studied. Abstract : Fluorescence‐based detection is a sensitive and rapid method for detecting and identifying potential threats such as nerve agents. Due to the highly toxic nature of the agents themselves, studies to develop sensors have normally involved simulants. However, care is needed when interpreting the results of studies using common simulants.